2014
DOI: 10.1016/j.bmc.2014.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, biological, and biophysical studies of DAG-indololactones designed as selective activators of RasGRP

Abstract: The development of selective agents capable of discriminating between protein kinase C (PKC) isoforms and other diacylglycerol (DAG)-responsive C1 domain-containing proteins represents an important challenge. Recent studies have highlighted the role that Ras guanine nucleotide-releasing protein (RasGRP) isoforms play both in immune responses as well as in the development of prostate cancer and melanoma, suggesting that the discovery of selective ligands could have potential therapeutic value. Thus far, the N-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 67 publications
(83 reference statements)
1
11
0
Order By: Relevance
“…In general, once Ras respond to a series of exterior and interior signals, it will subsequently amplify or turn on other factors, which ultimately regulate cell differentiation, growth, invasion, angiogenesis and survival; however, the Ras mutations are rare in tumors (15)(16)(17). Moreover, it was suggested that Ras could be constitutively overactivated by various upstream signaling elements, such as Ras guanyl nucleotide releasing peptides (RasGRPs) (18)(19)(20). Among them, RasGRP3 promotes guanine nucleotide exchange of H-Ras, R-Ras and Rap1 exerting oncogenic effects; and its overexpression or active form phospho-RasGRP3 were observed in numerous cancer types, regulating the proliferation, survival and migration of human solid tumors and several hematologic neoplasms (14,(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Instructionmentioning
confidence: 99%
“…In general, once Ras respond to a series of exterior and interior signals, it will subsequently amplify or turn on other factors, which ultimately regulate cell differentiation, growth, invasion, angiogenesis and survival; however, the Ras mutations are rare in tumors (15)(16)(17). Moreover, it was suggested that Ras could be constitutively overactivated by various upstream signaling elements, such as Ras guanyl nucleotide releasing peptides (RasGRPs) (18)(19)(20). Among them, RasGRP3 promotes guanine nucleotide exchange of H-Ras, R-Ras and Rap1 exerting oncogenic effects; and its overexpression or active form phospho-RasGRP3 were observed in numerous cancer types, regulating the proliferation, survival and migration of human solid tumors and several hematologic neoplasms (14,(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Instructionmentioning
confidence: 99%
“…27 We limited our comparison to RasGRP1, since both RasGRP1 and RasGRP3 closely resembled one another in binding affinity for aryl-DAG lactones 27 and for the DAG-indololactones in our previous study. 21 In general, none of the compounds were appreciably more potent than parent compound 1 for any of the studied proteins (Table 1). Although all compounds showed equal or stronger affinity for RasGRP1 than for PKCα, the obtained values of selectivity, ranging from 1 to 6.5-fold, indicated that none of the synthesized DAG-indololactones improved the selectivity of the parent compound 1 (22-fold in parallel measurements, Table 1).…”
Section: Resultsmentioning
confidence: 92%
“…Other studies have shown that RasGRP is a target of the anticancer drug ingenol-3-angelate (Song et al, 2013). On the basis of the interaction between cell analysis and biophysical analysis with a model membrane, Jelinek and Comin's groups synthesized DAG-indololactone analogs, wherein indole rings are linked to DAG in different positions (Garcia et al, 2014;Elhalem et al, 2017). Compound 39 (Figure 9), which has an indole substituted at the R3 position, presents excellent binding affinity and selectivity to RasGRP1 as evidenced by its ClogP value of 5.0 and selectivity for PKCα, PKCε, and RasGRP1 [the binding affinities of compounds for PKCα, PKCε, and RasGRP1 were determined in vitro by competition with bound (20-3H)phorbol 12,13-dibutyrate (PDBU) in the presence of 100 µg/mL phosphatidylserine (Elhalem et al, 2017)].…”
Section: Selective Activators Of Rasgrpmentioning
confidence: 99%